Clinical conditions and memory complaints in outpatient elderly - Magaldi,Regina Miksian (2008)
Abstract Memory complaints are common in elderly, and may be associated with many clinical problems. Objective: To identify clinical conditions and possible factors related to memory complaints in elderly outpatients presenting at a tertiary unit. Methods: Patients with memory complaints and normal cognitive screening tests were submitted to clinical and laboratorial testing. Radiological evaluation was performed as needed for diagnosis. Results: One hundred and seventy-seven subjects were initially evaluated, 12 were excluded because of poor and inconsistent memory complaints. Of the remainder, seventeen had criteria for dementia diagnosis. Ninety-two (55.4%) had one or more comorbid conditions possibly related to their complaints. Major depression was present in 26.0%. Sixteen patients (9.6%) had vitamin B12 deficiency, 8 were in use of inappropriate medications, and 7 (4.2%) had hypothyroidism. Other conditions diagnosed were: generalized anxiety disorder, obstructive sleep apnea syndrome, hyperparathyroidism, normal pressure hydrocephalus. Three patients had severe hearing loss (in 22 with hearing complaints); one had severe visual impairment (in 22 with visual complaints). Conclusions: Comprehensive evaluation was able to identify treatable conditions possibly related to memory complaints.